The university academies: an improvement science research platform for P-20 education - Odell, Michael; Kennedy, Teresa J.; Simmons, Jo Ann (Frontiers in Education, 2025)
The University of Texas at Tyler University Academy (UA) serves as an innovative case study in applying Improvement Science within a K-12 educational setting. This research examines how the UA, operating across rural, urban, and suburban campuses, has embedded the Plan-Do-Study-Act (PDSA) cycle to drive continuous improvement in student and teacher outcomes. Using Stake’s Holistic Case Study Approach, the study explores the UA as both an intrinsic case, valuable for its unique educational model, and an instrumental case, offering insights applicable to broader educational contexts. Drawing on foundational work in Improvement Science, including that of Douglas Engelbart and Anthony Bryk, this manuscript situates the UA within a rich historical and theoretical framework. It highlights key interventions, such as blended learning for literacy, Response to Intervention (RTI), and dual credit programs, are examined as case examples to illustrate how iterative, data-driven approaches are associated with improvements in student achievement and teacher professional development. The findings suggest that continuous refinement through Improvement Science may support effective instructional strategies and context-specific adaptations across diverse educational environments, providing insights for institutions considering similar evidence-based approaches.